Angiotensin‐II receptor 1 antagonist fetopathy – risk assessment, critical time period and vena cava thrombosis as a possible new feature. (5th February 2013) - Oppermann, Marc; Padberg, Stephanie; Kayser, Angela; Weber‐Schoendorfer, Corinna; Schaefer, Christof
<x xml:space="preserve">Abstract</x> Aims Angiotensin‐II receptor 1 antagonists (AT1‐antagonists) may cause severe and even lethal fetopathy in late pregnancy. However, exposure still occurs in spite of warnings in package leaflets. This study aimed to assess the risk of fetopathy, the sensitive time window, and possible new symptoms in prospective as well as retrospective cases with AT1‐antagonist treatment during the second or third trimester of pregnancy. Methods Patients were enrolled by the Berlin Institute for Clinical Teratology and Drug Risk Assessment in Pregnancy between 1999 and 2011 through risk consultation. Symptoms defined as indicative of AT1‐antagonist fetopathy were: oligo‐/anhydramnios, renal insufficiency, lung hypoplasia, joint contractures, skull hypoplasia and fetal/neonatal death. Results In 5/29 (17%) prospectively enrolled cases with AT1‐antagonist exposure beyond the first trimester oligo‐/anhydramnios was diagnosed. Two infants showed additional symptoms of fetopathy. The risk is more than 30% if treatment continues beyond the 20th week of pregnancy. Oligo‐/anhydramnios was reversible after AT1‐antagonist withdrawal. Among 16 retrospective case reports, three infants presented with a thrombosis of the inferior vena cava in the vicinity of the renal veins. Four out of 13 live births did not survive. Conclusions Our survey suggests that the risk increases with duration of AT1‐antagonist treatment into late pregnancy and oligo‐/anhydramnios may be reversible after AT1‐antagonist discontinuation. Thrombosis of inferior vena cava may be a new feature of AT1‐antagonist fetopathy. AT1‐antagonist medication during pregnancy constitutes a considerable risk and must be discontinued immediately. In case of indicative diagnostic findings in either the fetus or newborn, previous maternal AT1‐antagonist exposure should be considered.